Long-term survival follow-up of atezolizumab in combination with platinum-based doublet chemotherapy in patients with advanced non–small-cell lung cancer. (September 2018) - Liu, Stephen V.; Camidge, D. Ross; Gettinger, Scott N.; Giaccone, Giuseppe; Heist, Rebecca S.; Hodi, F. Stephen; Ready, Neal E.; Zhang, Wei; Wallin, Jeffrey; Funke, Roel; Waterkamp, Daniel; Foster, Paul; et al.
Abstract: Background: Before the availability of immunotherapy, chemotherapy was standard first-line therapy for non–small-cell lung cancer (NSCLC) lacking actionable gene alterations. Preclinical evidence suggests chemotherapy is immunomodulatory, supporting chemotherapy/immunotherapy combinations. Atezolizumab, anti-programmed death ligand-1 (PD-L1) antibody, blocks programmed cell death protein-1 and B7.1 interaction with PD-L1. GP28328 (NCT01633970 ) assessed atezolizumab with chemotherapy in multiple tumours; we report results for advanced, treatment-naïve NSCLC. Methods: Patients received atezolizumab plus carboplatin with paclitaxel (Arm C: atezo/cb/pac), pemetrexed (Arm D: atezo/cb/pem, maintenance pemetrexed permitted), or nab-paclitaxel (Arm E: atezo/cb/nab-pac), four–six cycles, then atezolizumab maintenance. Primary end-point was safety; secondary end-points were objective response rate (ORR), progression-free survival (PFS) and overall survival (OS). Results: Seventy-six NSCLC patients were enrolled (n = 25, 25 and 26 for Arms C, D and E, respectively). Common treatment-related grade III/IV adverse events were neutropenia (36% atezo/cb/pac, 36% atezo/cb/pem, 42% atezo/cb/nab-pac) and anaemia (16% atezo/cb/pac, 16% atezo/cb/pem, 31% atezo/cb/nab-pac). Confirmed ORRs were 36% atezo/cb/pac, 68% atezo/cb/pem (one complete response [CR]) and 46% atezo/cb/nab-pac (four CRs). Median PFS was 7.1 months, (95% confidence interval [CI]: 4.2–8.3), 8.4 months (95% CI: 4.7–11) and 5.7 months (95% CI: 4.4–14.8), respectively. Median OS was 12.9 months (95% CI: 8.8–21.3), 18.9 months (95% CI: 9.9–27.4) and 17.0 months (95% CI: 12.7–not evaluable), respectively. Conclusion: Atezolizumab with chemotherapy was well tolerated with encouraging efficacy, though the analysis was limited by small numbers. NSCLC chemotherapy combination studies are ongoing. ClinicalTrials.gov identifier: NCT01633970 . Highlights: Atezolizumab in combination with platinum-doublet chemotherapy was well tolerated. Median progression-free survival ranged from 5.7 to 8.4 months. Overall survival ranged from 12.9 to 18.9 months. Despite small numbers, efficacy supports further investigation.